Analysis of China's Regional Economic Vitality and Its Influential Factors Based on System Cluster Model and Computer Multiple Regression Model. (May 2020) - Pang, Jinfeng; He, Jintao; Luo, Lan; Li, Yao; Mao, Yiren; Zhang, Hanrui
Abstract: The economic vitality of China's regions (provinces or cities) is affected by many factors. In this paper, the influencing indicators are listed by referring to the relevant factors that affect economic vitality. Based on the data obtained from the Internet, a systematic (hierarchical) clustering model of relevant indicators in Chinese provinces and cities is established, introducing the Elbow Rule and Factor Analysis to analyze and summarize the correlation of various indicators. A computer-based multiple regression model is used to establish a relationship model that affects economic vitality. Based on this relationship model, effective and reasonable suggestions for improving economic vitality are proposed.